Curcumin Suppresses Lipopolysaccharide-Induced Cyclooxygenase-2 Expression by Inhibiting Activator Protein 1 and Nuclear Factor κB Bindings in BV2 Microglial Cells - Gu Kang; Pil-Jae Kong; Young-Jin Yuh; So-Young Lim; Sung-Vin Yim; Wanjoo Chun; Sung-Soo Kim (Elsevier, 2004)
Inflammation is a significant component of chronic neurodegenerative diseases. Cyclooxygenase-2 (COX-2) is expressed in activated microglial cells and appears to be an important source of prostaglandins during inflammatory conditions. To investigate the effect of curcumin on COX-2 gene expression in microglial cells, we treated lipopolysaccharide (LPS)-challenged BV2 microglial cells with various concentrations of curcumin. Curcumin significantly inhibited LPS-mediated induction of COX-2 expression in both mRNA and protein levels in a concentration-dependent manner. COX-2 enzyme activity was also inhibited in accordance with mRNA and protein levels. Furthermore, curcumin markedly inhibited LPS-induced nuclear factor κB (NF-κB) and activator protein 1 (AP-1) DNA bindings. These data suggest that curcumin suppresses LPS-induced COX-2 gene expression by inhibiting NF-κB and AP-1 DNA bindings in BV2 microglial cells. Keywords:: curcumin, cyclooxygenase-2, microglia